2019
DOI: 10.1002/ep.13243
|View full text |Cite
|
Sign up to set email alerts
|

Chemical synthesis of materials based on calcium zirconate for solid oxide fuel cells (SOFC)

Abstract: Fuel cells allow the production of energy from a clean electrochemical reaction. Among various types, the solid oxide fuel cell (SOFC) operates at high temperatures, allowing the conversion of hydrogen fuel into electricity, where water is generated as a by‐product. Strontium‐doped lanthanum manganite (La1‐xSrxMnO3, LSM) is commonly used as a cathodic material in traditional high‐temperature solid oxide fuel cells. Nowadays, the operating temperature of SOFCs should be reduced to 600–800°C due to improved fine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…[55] It was shown that increasing Sr concentration up to x = 0.5 in LSM matrix for LSM-YSZ composites is advantageous for both electronic conductivity and polarization resistance. [5,[56][57][58] Nevertheless, normally, compositions ranging from x = 0.15 to x = 0.2 are chosen due to their mechanical suitability with YSZ. [58] Ananyev et al [59] also developed LSM-YSZ composite cathode for SOFC.…”
Section: Lsm-based Perovskite Materials As Cathodementioning
confidence: 99%
“…[55] It was shown that increasing Sr concentration up to x = 0.5 in LSM matrix for LSM-YSZ composites is advantageous for both electronic conductivity and polarization resistance. [5,[56][57][58] Nevertheless, normally, compositions ranging from x = 0.15 to x = 0.2 are chosen due to their mechanical suitability with YSZ. [58] Ananyev et al [59] also developed LSM-YSZ composite cathode for SOFC.…”
Section: Lsm-based Perovskite Materials As Cathodementioning
confidence: 99%
“…Last, SOFCs operate at the highest temperatures of the discussed fuel cells with temperatures of 800-1,000 • C (Figure 1) to facilitate the mass transfer through the solid electrolyte layer (Vieira et al, 2019). The electrolyte layer is an ion-conducting solid-electrolyte that is layered between the two porous electrodes (Mahato et al, 2015).…”
Section: Basic Principlesmentioning
confidence: 99%